Evaluation of Different Variables of Agression Levels of Physical Education and Sports School and Educational Faculty Students - Serkan Hazar; Ercan Polat; Zekihan Hazar (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the aggressiveness of the students who are studying at the Faculty of Education and the School of Physical Education and Sports. In this research, which adopted the quantitative research model, the relational search pattern was used. In this context, a total of 213 people, 104 female and 109 male, participated in the survey. The "Buss Perry Aggression Scale" was adapted by Can (5) to determine the level of aggression of participants in the study. SPSS 20 program was used in the analysis of the data. In the analysis of the data, T test was used to examine the difference between two independent variables and aggression attitudes. Pearson corelation was used to test the relationship between variables. According to the findings, it was determined that there is a significant relationship between the aggressiveness levels of the individuals and gender and type of sport that they made. It was seen that there was no meaningful relationship between age, the part of education, whether or not doing sports, the frequency of doing sports and the duration of sports. It has been determined that male individuals are higher in physical aggression subscale than female individuals. When the relationship between the department where they are educated and the aggressiveness is examined, it is determined that the students who are studying at the Physical Education and Sports are higher than the students who are educated at the 492 Faculty of Education in the physical aggression sub-dimension. It is determined that the students who play sports are higher than the students who play sports in all sub dimensions of sports students. As a result; the fact that aggression behaviors differ according to various variables, but the fact that there is not a statistically significant difference between participants who do sports and those who do not, is quite striking in contradiction with various theories in the field.